Editor's note - Buško, Vesna (Array, 2004)
Writing the words of Editorial is always an extraordinary matter. This ought to be among the most pleasurable and exciting moments in putting the last touches on the new issue of a journal. And the delight was supposed to come about to the Review’s newly elected Editor-in-Chief Professor Alija Kulenović. This time, though, it turned out to be probably the most sorrowful portion of the process of creating and finalizing a journal issue ever. At least, this is definitely true for me. This is the first volume of the Review of Psychology as conceived and supposed to be edited by him. And what I was doing last weeks and months by proceeding the work of giving rise to the incoming Review’s volume was just one of my miserable tries to overcome the deep emptiness I have felt enduringly, and no less than to pretend like we held the power do the job in a way he thought of. About a year ago, Professor Alija Kulenović accepted to serve as the Editor-in-Chief starting with this 11th volume of the Review. At that time he told me that he accepted it conditionally – provided I take on to be the deputy. He knew I would, and I agreed of course immediately since I knew that any kind of collaboration with him must have been an invaluable professional and learning experience. As soon as he took on the editorial enterprise he started generating ideas on how to attract researchers from different fields of psychology as well as from different countries within and outside the region to submit their work to the Review. He took advantage of any opportunity to talk to other colleagues about it. He listened readily to their opinions and reflected on their suggestions as to how to put together different issues and volumes. He thought of and searched for a form and a content outline of the journal that would reveal in a way the uniqueness of the region. One of his main points and aspirations in this regard was to manage to adjust the thematic profile and features of the Review to fit in the requirements needed to be covered by important indexing and citation services. Out of some of these discussions an idea on preparing selected thematic issues came out. Hence, the following volume of the Review was decided to include a special issue on social psychology research approaches and methodology. As the main editing activities including those related to this thematic issue have already been started and lead by Professor Alija Kulenović, the next volume of the Review will still be published under his name as the Editor-in-Chief. And there is not so much to be added now about the contents of the next volume but to assure that we will do our utmost and hope to come closer to his standards of excellence in this task. Finally, I would like to note that many persons contributed in one way or another to the appearance of this issue. I wish to thank greatly to all of them: this applies to all the reviewers of the articles, the authors of the contributions, the publisher who patiently waited for the manuscripts to be prepared for the first print, the designer who generously offered us several versions of the cover page, the new Review’s assistant Ivana Hromatko who usually managed to complete the work right after I thought of asking for assistance, and all the colleagues who eagerly helped with advices on any question I might have considered last months concerning the Review. Particular thanks go to Professor Vladimir Kolesarić, the Editor-in-Chief of the previous ten years of the Review, and Dr. Dragutin Ivanec for their thoughtful help and encouragement they were giving us in preparing this issue.